1992
DOI: 10.3109/02713689209033492
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced retinopathy in the rat: hemorrhages and dysplasias may lead to retinal detachment

Abstract: Rearing neonatal rats in hyperoxia induces the development of retinal hemorrhages and retinal dysplasia. Albino rats were placed in 80% oxygen immediately after birth and were exposed for either 5, 10, or 14 days, followed by sacrifice or exposure to normoxia for an additional 2, 4, 5, 7, 8, 10, 38, 45 or 56 days. Control rats were simultaneously raised in room air and sacrificed at the same times. All animals were enucleated and their eyes processed for light and electron microscopy. Eyecups were trimmed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…ROP is a multifactorial disease and numerous risk factors in addition to light and oxygen such as xanthine administration, vitamin E de®ciency, gestational agebirth weight (Zierler 1988;Hammer et al, 1986;Sira et al, 1985) have been reported. A number of these suggested risk factors are consistent with an oxidative mechanism of injury; the lack of su cient antioxydant, such as vitamin E (Penn et al, 1992), would be expected to exacerbate the severity of oxidative retinal damage. Indeed the prophylatic administration of vitamin E, an oxygen reactive product, reduces the incidence and severity of ROP (Quinn et al, 1990) Lck tyrosine kinase may prevent excess reactive oxygen production and thus, may be necessary for normal retinal physiology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ROP is a multifactorial disease and numerous risk factors in addition to light and oxygen such as xanthine administration, vitamin E de®ciency, gestational agebirth weight (Zierler 1988;Hammer et al, 1986;Sira et al, 1985) have been reported. A number of these suggested risk factors are consistent with an oxidative mechanism of injury; the lack of su cient antioxydant, such as vitamin E (Penn et al, 1992), would be expected to exacerbate the severity of oxidative retinal damage. Indeed the prophylatic administration of vitamin E, an oxygen reactive product, reduces the incidence and severity of ROP (Quinn et al, 1990) Lck tyrosine kinase may prevent excess reactive oxygen production and thus, may be necessary for normal retinal physiology.…”
Section: Discussionmentioning
confidence: 98%
“…Retinal dysplasia with rosette formation has previously been associated with the loss or absence of retinal pigment epithelium (RPE) (Silverstein et al, 1971) or RPE function. Dysplasia and rosettes have been reported as features of oxygen-induced retinopathy in the rat model for retinopathy of prematurity (ROP) (Penn et al, 1992) and by photosensitization induced retinopathy in the newborn Beagle (Sadda et al, 1994). Rosettes have also been decribed in the retinoblastoma (Flexner 1981;Ts'o 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this model is also considered an accepted model for diabetic retinopathy [16]. Previous studies have shown that compared to mice, rats are less prone to develop ischemiainduced retinal neovascularization, and require cycling between hypoxia and normoxia to develop signi¢cant retinal neovascularization [21,22]. However, most of these previous studies used Sprague Dawley rats [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…When the rat pup is placed back into normal air at a later stage, the retina is rendered hypoxic because of the lack of normal vessel development, and consequently epiretinal angiogenesis develops, ultimately leading to retinal detachment and blindness [19][20][21].…”
Section: Vascular Pathology During Oxygen-induced Retinopathymentioning
confidence: 99%